DISTRICT ROAD DATABASE MANAGEMENT BASED ON GEOGRAPHIC INFORMATION SYSTEM TO SUPPORT REGENCY ROAD MAINTENANCE (CASE STUDY: SINTANG DISTRICT) - Kurniawan, Yengkie; Widodo, Slamet (Fakultas Teknik Universitas Tanjungpura, 2023)
Road maintenance on the section of the road classified as a district road in the Sintang sub-district is the responsibility of the Sintang District Government. The financial constraints of the Sintang District Government, allocated annually in the Regional Revenue and Expenditure Budget (APBD) of Sintang District, pose a challenge in realizing the plan for district road maintenance, whereas funding for road maintenance needs to be budgeted regularly to maintain the road conditions in good shape, therefore, in this case, stakeholders or decision-makers are expected to be able to consider and decide which road sections should receive recommendations for